Spatial Planning Policy in the Control Aspect of Urban Area Development - Permana, Danny (International Journal of Science and Society, 2023)
The rapid development of urban areas has the potential to cause various problems, including environmental degradation, excessive population density, and infrastructure imbalances. Spatial planning policies are an important key in controlling urban development to achieve a balance between economic growth and environmental sustainability. However, challenges in implementing these policies are often related to inter-agency coordination and compliance with existing regulations. This research aims to analyze the effectiveness of spatial planning policies in controlling urban development. This research uses a qualitative approach with data originating from relevant previous studies, which are then analyzed to gain a deeper understanding. The conclusion of this research shows that spatial planning policies play a vital role in controlling sustainable urban development. Integration of spatial planning policies with other policies, such as transportation and housing, is needed to create effective synergies. Active participation of all stakeholders, including civil society, is essential in the policy-making process to ensure sustainability and fairness. The main challenges identified relate to divergent sectoral interests and a lack of inter-agency coordination. Sustainable urban development requires a joint commitment to overcome these challenges and implement comprehensive and inclusive spatial planning strategies.